Multifractal Formalism in Tasks of Dynamic Plasticity - Kuznetsov Aleksander (EDP Sciences, 2021)
The application of the multifractal parameterization method for comparing structural changes observed in an optical microscope on steel St.3 subjected to severe plastic deformation and high-rate superplastic deformation is investigated.